The Cesar C. Climaco political leadership - Evangelista, Servando Marquez
This is a study on the political leadership of Cesar C. Climaco a four-term mayor and assemblyman of Zamboanga City. The objectives of the study were to determine the political milieu of Climaco's career, explain the qualities and sources of political strenght of Climaco. Also to describe the political organizations which he headed and participated in, as well as his repertoire of political strategies. The researcher also sought to determine his role as an anti-Marcos leader., To achieve the objectives, the researcher used three methods; library research, interview with key informants, and questionnaires to be answered by respondents in Zamboanga City. The researcher found out that as a political figure Climaco was close to the people. He was a hands-on type of mayor that was very willing to serve his constituents and, he had a unique repertoire of political strategies. It was found out that Climaco was an ardent fighter against the Martial Law regime. The Concerned Citizens Aggrupation (CCA) was the party he headed and that the issues of basic human rights and graft and corruption were the focus of Climaco's political leadership.